Efficient Sourcing and Debt Financing in Imperfect Product Markets - Subramaniam, Venkat (Management Science, 1998)
Supplier relations play an important role in determining a firm's product market strategy and position, by affecting the cost and quality of the product produced by the firm. These relations are especially significant because the cost of purchased materials for an average firm is more than half its total sales. In this paper, we model the adverse incentives of a firm that sources from a competitive supplier industry. We show that a firm's propensity to behave opportunistically towards its suppliers raises the firm's input costs by decreasing the number of suppliers servicing it. This results in a suboptimal production decision compared to the firm's first best choice. We argue that an appropriate level of debt financing alters the shareholder incentives and mitigates the hold-up problem. Further, we also show that at the optimal debt level, the firm produces its first best level of output.